STRATEGI GURU MENGGUNAKAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN ARTIKULASI ANAK USIA 5-6 TAHUN DI TK ANGKASA LANUD EL TARI KUPANG - Iba, Florida; Budiman Jama, Karolus; Nama Koten , Angelikus; G Betty, Credo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the teacher's strategies in using audio-visual media to improve the articulation ability of children aged 5-6 years at TK Angkasa Lanud El Tari Kupang. The background of this research was based on the finding that 2 out of 16 children in group B2 experienced articulation disorders, characterized by mispronunciation of consonants R as L, K as T, and G as D. A descriptive qualitative approach was employed. Data were collected through participatory observation, semi-structured interviews, and documentation. Data validity was tested using technical triangulation. The results show that the teacher applied planned and systematic strategies through several stages: (1) lesson planning that explicitly includes audio-visual media in the teaching module; (2) media selection comprising YouTube animation videos, children’s songs, and age-appropriate colorful images; (3) implementation of learning using direct imitation, individual feedback, and repeated practice; and (4) evaluation and follow-up through daily observation and communication with parents. Audio-visual media proved effective in increasing children’s motivation, enthusiasm, and pronunciation ability, including visible progress in a child who previously said “lumah” beginning to attempt “rumah”. It is concluded that the planned, consistent, and needs-based use of audio-visual media is an effective strategy for improving early childhood articulation ability. Keywords: teacher strategy, audio-visual media, articulation ability, early childhood, PAUD